Kinerja Dinas Kesehatan dalam Mengawasi Kualitas Air Minum di Kota Padang - Rila Amisa; Adil Mubarak (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This research was done in Health Office Padang City, Which purpose to discover about to performance of the Padang City Health Office and the inhibiting factors in monitoring the quality of drinking water in the Padang City. The study applies a qualitative method using purposive sampling. Prosess aggregation data colth pass through observation, interview, and study documentation, while technique for validity the data testing that using resource triangulation with data analysis such as a data collection, data reduction, data presentation along with pulling conclusions. The results of the research conducted was explain performance of the Health Office in Supervising the Quality of Drinking Water in the City of Padang is not optimal, because there are still obstacles such as: Lack of supervision and attention from the Health Office to the community regarding the quality of drinking water that is fit for consumption, there are still limited funds, materials and tools for examining water samples, Besides that, there are also limited human resources so that all work in a certain section is held by only one person. It can be concluded that the performance of the Health Office has not been maximal in monitoring the quality of drinking water in Padang City.